1998
DOI: 10.1021/bi972062g
|View full text |Cite
|
Sign up to set email alerts
|

Structural Coupling of Troponin C and Actomyosin in Muscle Fibers

Abstract: EPR of spin labeled TnC at Cys98 was used to explore the possible structural coupling between TnC in the thin filament and myosin trapped in the intermediate states of ATPase cycle. Weakly attached myosin heads (trapped by low ionic strength, low temperature and ATP) did not induce structural changes in TnC as compared to relaxed muscle, as spin labeled TnC displayed the same narrow orientational distribution [Li, H.-C., and Fajer, P. G. (1994) Biochemistry 33, 14324]. Ca2+-binding alone resulted in disorderin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In skinned fibers, does the increase in TnC affinity reflect C-domain conformational changes induced by the attachment of rigor bonds to the thin filament? This hypothesis finds support in experiments showing that the orientation of TnC labeled in the central helix is more perpendicular to the fiber axis in the presence of rigor bonds [19,20,38]. Another clue comes from the decrease in the cooperativity of rTnC binding curves in the presence of strong bridges (Fig.…”
Section: Rigor Cross-bridges Enhance Tnc Bindingmentioning
confidence: 64%
See 1 more Smart Citation
“…In skinned fibers, does the increase in TnC affinity reflect C-domain conformational changes induced by the attachment of rigor bonds to the thin filament? This hypothesis finds support in experiments showing that the orientation of TnC labeled in the central helix is more perpendicular to the fiber axis in the presence of rigor bonds [19,20,38]. Another clue comes from the decrease in the cooperativity of rTnC binding curves in the presence of strong bridges (Fig.…”
Section: Rigor Cross-bridges Enhance Tnc Bindingmentioning
confidence: 64%
“…Several studies have shown that both Ca 2+ and cross-bridges can change the N-domain conformation of TnC on the thin filament. In skeletal and cardiac muscle fibers that incorporate labeled TnC, cycling cross-bridges can also affect TnC structure [1,14,15,[18][19][20][21]48]. Probes attached to the C-domain are also sensitive to both cycling and rigor cross-bridges [38].…”
Section: Introductionmentioning
confidence: 99%
“…These major rotational correlation times were slower than the time (7 ns) of the Cys98 residue of rabbit skeletal TnC in a sucrosefree solution. 34,35 In order to monitor how the residues are buried in TnC, we measured the solvent-accessibility of Cys84-MTSSL in the monomer state. P1/2 is the power at which EPR spectral peak-to-peak width is one-half of its saturated value (see Materials and Methods).…”
Section: Mobility Of Cys35-mtssl or Cys84-mtssl Of Hctnc In The Monommentioning
confidence: 99%
“…[20][21][22][23] Although in vitro structures are available for most of the troponin components and their complexes, obtained by X-ray, NMR and FRET methods, it is important to observe dynamic interactions in the complexes in situ. Electron paramagnetic resonance (EPR) is a powerful tool for measuring the mobility of spin labels attached to a domain in a protein, [24][25][26][27][28][29][30] by determining the angle of spin label toward a magnetic field [31][32][33][34][35] and the distance between two spin labels. 36,37 The methods for exchange of TnC and myosin light chain in muscle fibres [38][39][40] have made it possible to follow the conformational changes of TnC or myosin neck in permeabilized muscle fibre systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation